Revealing middle school students’ misconceptions about basic astronomy concepts through drawing method - Koca, Ece Ebrar (My University, 2019)
The main purpose of this study is to reveal middle school students’ misconceptions about basic astronomy concepts. The study was conducted in a public school in Gaziantep. The study was carried out with 181 middle school students. The students were from six different classes. Each of two classes was from 6th, 7th and 8th grades, respectively. A hundred of the students were female and the others were male. This study is based on a qualitative research method. In this research method, students were asked questions about basic astronomy concepts and were asked to answer these questions by drawing. After the students’ drawings, interviews were also utilized in order to clarify students’ drawings and to probe students’ understandings. According to the results of the study, a wide variety of misconceptions about astronomy concepts were revealed. The main findings showed that students have lack of knowledge about sizes of the Earth and moon, how the solar and lunar eclipses take places, celestial bodies in the eclipses and difficulty about vitalization of the eclipses in their minds.

Bu çalışmadaki asıl amaç fen bilimleri dersinde yer alan temel astronomi konularındaki ortaokul öğrencilerinin sahip oldukları kavram yanılgılarını ortaya çıkarmaktır. Çalışma Gaziantep Türkiye‘deki bir devlet okulunda gerçekleştirilmiştir. Çalışma iki 6.sınıf, iki 7. sınıf ve iki 8.sınıf olmak üzere toplam altı sınıfta, 181 sayıda öğrenciyle gerçekleştirilmiştir. Öğrencilerin 100‘ü kız, diğerleri ise erkektir. Çalışma kapsamında öğrencilere astronomi konuları ile ilgili sorular sorulmuş ve cevaplarını çizerek ifade etmeleri istenmiştir. Çalışma nitel bir çalışmadır. Çalışmada öğrencilerin temel astronomi konularındaki kavram yanılgılarını çizim yöntemiyle tespit etmek amaçlanmıştır. Öğrencilerin çizimlerinin ardından, çizimlerini netleştirmek ve öğrencilerin anlamalarını sorgulamak için görüşme verilerinden yararlanılmıştır. Öğrencilerin çizimlerinde ayın dünyadan daha büyük, dünyanın aydan daha büyük olduğunu ifade eden çizimlere; güneş tutulmasıyla ay tutulmasını birbirine karıştırdıklarına, tutulmalarda yer alan gök cisimlerini tam olarak bilmediklerine ve de tutulmaların nasıl gerçekleştiğini zihinlerinde canlandıramadıkları ve çizimlerine yansıtamadıkları sonucuna ulaşılmıştır.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Temel astronomi konuları; Çizim yöntemi; Kavram yanılgıları; Fen eğitimi; Basic astronomy concepts; Drawing method; Misconceptions; Science education